Pleistocene origin and colonization history of Lobelia columnaris Hook. f. (Campanulaceae: Lobelioideae) across sky islands of West Central Africa. Issue 22 (20th October 2021) - Pérez‐Pérez, Miguel A.; Yu, Wen‐Bin
Abstract: We aimed to infer ancestral area and historical colonization of Lobelia columnaris in the sky islands of Bioko and Cameroon through dated phylogeny using chloroplast genomes. Specifically, we aim to answer the following questions: (1) What are the phylogenetic relationships among Bioko Island and Cameroon populations? (2) Are the older populations found in the older sky islands? We assembled novel plastomes from 20 individuals of L. columnaris from 5 mountain systems. The plastome data were explored with phylogenetic analyses using Maximum Likelihood and Bayesian Inference. The populations of L. columnaris have a monophyletic origin, subdivided into three plastomes‐geographic clades. The plastid phylogenomic results and age of the sky islands indicate that L. columnaris colonized first along with the Cameroon Volcanic Line's young sky islands of Bioko. The crown group (1.54 Ma) split the population in Bioko and mainland Cameroon. It is possible that Bioko was the ancestral area and likely isolated during cold and dry conditions in forest refugia. Presumably, the colonization history occurred during the middle‐late Pleistocene from South Bioko's young sky island to North Bioko and the northern old sky islands in Cameroon. Furthermore, the central depression with lowland forest between North and South Bioko is a current geographic barrier that keeps separating the populations of Bioko from each other. Also, the shallow sea channel keeps isolated the populations of Bioko and the mainland populations. The Pleistocene climatic oscillations led to the divergence of the Cameroon and Bioko populations into three clades. L. columnaris colonized the older sky islands in mainland Cameroon after establishment in Bioko's younger sky islands. Contrary to expectations, the biogeography history was an inverse progression with respect to the age of the Afromontane sky islands. Abstract : Lobelia columnaris colonized the sky island of West Africa during the Pleistocene. The colonization history of this giant lobelia was from the young sky islands through old sky islands in mainland Africa.